The level of organizational citizenship behavior for female primary school teachers in Buraydah - Alsamani, Luluh Ibrahem Ali (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the level of organizational citizenship behavior among primary school teachers in the city of Buraidah from their point of view, and to reveal the existence of statistical significance differences attributable to the two variables (years of experience, specialization), and the study used the survey descriptive approach, and the tool was represented in the scale developed ( niehoff & moorman, 1993) to collect data, and it was applied to a simple random sample of 334 female teachers, and the results reached showed that the level of organizational citizenship behavior for primary school teachers in Buraidah obtained a total average (4.04 out of 5), that is, to a large degree, At the dimensional level; After civility, the highest mean was obtained (4.38), followed by civilized behavior with an average (4.24), both with an estimate (very large), followed by the conscience dimension with an average (4.05), then altruism after an average (4.04) and finally The mathematical dimension is an average of (3.48) and it is all rated (large), while the proposals got an average of (2.64 out of 3), i.e. important (with a great degree). There are also statistically significant differences in the level of organizational citizenship behavior attributable to the different years of experience, while there are no statistically significant differences in the level of organizational citizenship behavior due to the difference in specialization, except for the dimension of the conscience in favor of scientific specializations, and based on the results a set of recommendations and proposals were made to improve the level of organizational citizenship behavior for female primary school teachers in the city of Buraidah and the whole of the Kingdom.